An economical and specific purification process of human haptoglobin 1-1. (October 2022) - Zang, Jiatao; Wu, Yue; Li, Qinghui; Zhang, Zisen; Xiang, Xinming; Peng, Xiaoyong; Liu, Liangming
Abstract: Human haptoglobin (Hp) 1–1 is a potential protein drug to eliminate toxic effects of free hemoglobin, however it was difficult to selectively purify Hp 1–1 from pooled plasma. In this work, a specific purification process of Hp 1–1 from pooled human plasma was introduced, with PEG precipitation as the key step. First, frozen human plasma was thawed on ice to remove condensed proteins, then Hp 1–1, Hp 2–1 and Hp 2–2 were all precipitated by ammonium sulfate between 40%–65% (0 °C) saturation. 50% (m/v) PEG4000 solution (dissolved in 0.2 M HAc-NaAc pH 5.0) was then added into the pellet resuspension, and Hp 2–1, Hp 2–2 were precipitated between the concentration of 6%–15% (m/v) while Hp 1–1 remained in the 15% supernatant. The purity of Hp 1–1 raised from < 5% to a maximum of 50% after this step. Finally, Hp 1–1 with a maximum purity of > 98% was prepared after refined purification including anion exchange chromatography and hydrophobic chromatography. This process has a total Hp 1–1 recovery of 76.97%, along with characteristics of low cost, high efficiency, and high output, making it a process applicable for large-scale purification of Hp 1–1 from human plasma. Graphical Abstract: ga1 Highlights: Hp 1–1 was selectively purified from pooled human plasma containing three subtypes. PEG4000 could separate human Hp 1–1 from Hp 2–1 and Hp 2–2. Hp 1–1 could be purified economically in large-scale with high purity and recovery.